Hubungan Tingkat Pengetahuan dan Sikap Ibu tentang Status Gizi pada Balita - Florensia Cia; ‪Melisa Frisilia; Indriani Indriani (Jurnal Surya Medika (JSM), 2022)
Nutritional status is a measure of the condition of a person's body that can be seen from the food consumed and the use of nutrients in the body. Knowledge is what is known and knowledge obtained by someone. Attitude is a reaction or response that is still closed from a person to a stimulus or object. The phenomenon found is the problem of nutritional status in toddlers with the relationship between the level of knowledge and attitudes of mothers about nutrition for toddlers. The aim of this study was to determine the relationship between the level of knowledge and attitudes of mothers about the nutritional status of children under five. Based on the results of research using literature reviews from six journals of the relationship between Mother's Knowledge Level and Attitude About Nutritional Status in Toddlers in respondents with less dominant categories and statistical results showed p-value = < 0.005. This shows that there is a relationship between the level of knowledge and attitudes of mothers about the nutritional status of toddlers. Based on the results of research, knowledge, and attitudes are closely related, because the higher a person's knowledge, the better the attitude that a person gets.